Makna dan Nilai di Balik Tradisi Maddoja Bine pada Masyarakat Tanete Rilau Kabupaten Barru - Nur Azizah Usman (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2018)
This study aims to determine the perception, value and social changes in the implementation of Maddoja Bine tradition for the people of Tanete Rilau District. This research used observation, interview and documentation method. The results showed that the community considered the ritual of land including Maddoja Bine is an obligation that must be met in accordance with the ancestral mandate. The noble cultural values ​​which up to now are maintained by the community are closely related to the teachings of the series which include religious values, socio-cultural values, and economic value and educational value. Changes that occur in Maddoja Bine tradition can be seen from the social and economic influence of a society.